2015
DOI: 10.1167/iovs.14-15708
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resveratrol on Protecting Corneal Epithelial Cells from Cytotoxicity Caused by Moxifloxacin and Benzalkonium Chloride

Abstract: The protective effects of antioxidant agents indicate that MOX, similar to BAC, causes oxidative stress-related cell damage. The results also inspired us to think about a "supplementary regimen" to increase safety and decrease the adverse effect in the treatment of corneal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Recently, mounting evidence has demonstrated that RSV may serve as a promising therapeutic reagent in a variety of acute and chronic neurodegenerative diseases [17,20,31,32,33]. It has been proven that RSV has various pharmacological functions such as anti-inflammatory, anti-oxidant, anti-apoptotic, anti-bacterial, and anti-cancer properties [20,32,34,35,36]. Among these beneficial roles, the anti-inflammatory property is significant in the neuroprotective effect of RSV.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mounting evidence has demonstrated that RSV may serve as a promising therapeutic reagent in a variety of acute and chronic neurodegenerative diseases [17,20,31,32,33]. It has been proven that RSV has various pharmacological functions such as anti-inflammatory, anti-oxidant, anti-apoptotic, anti-bacterial, and anti-cancer properties [20,32,34,35,36]. Among these beneficial roles, the anti-inflammatory property is significant in the neuroprotective effect of RSV.…”
Section: Discussionmentioning
confidence: 99%
“…[66] Cells exhibited ∼100% viability after incubation with F-Cip 1 and 2 , and Cip with concentrations up to 10 μM compared to cells without any treatment. Benzalkonium chloride is known to be cytotoxic [74-76] and killed ∼100% cells and served as control. There was no significant difference among Cip, 1 and 2 , indicating that modification of Cip with a fluorous tag did not change its cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, others revealed that treatment with resveratrol, a natural SIRT1 activator, restored VEGF secretion in RPE cells upon oxidative and inflammatory conditions [48]. Recent literature reported the anti-aging effect of resveratrol in cutaneous, endothelial and corneal wound healing [49][50][51]. In addition to antioxidant and anti-inflammatory properties, resveratrol stimulates SIRT1 activity through allosteric interaction and increases SIRT1 affinity for both NAD+ and the acetylated substrate [28,29].…”
Section: Discussionmentioning
confidence: 99%